An Automated Script Classification System Using Structure Optimization with Firefly Algorithm - S. Suganya, T.; S. Murugavalli, Dr. (International Journal of Engineering and Technology, 2018)
The Tamil language is very ancient one with a very rich literature. Several writers used many different materials such as copper plates, mural paintings, conch shells, cloth, palm leaves, wood, and pottery, metal and stone for encrypting their writing. Any information that was gathered from such inscriptions has given us plenty of knowledge on education, administration, economic tax, religion, culture, history, and astronomy. All these epigraphical inscriptions have played a critical role in revealing the knowledge on past civilization and the character classification that belongs to the different time periods. This way, the system has been proposed for reading all ancient Tamil characters which belong to different periods by means of testing a very small amount of these characters in the Tamil language. All the characters that are examined have been obtained from the script and have been coordinated with all characters that belonged to the different periods by using machine intelligence. Thus, this system proposed contained several modules like the like segmentation, extraction of features, pre-processing, binarization, and acquisition of image, prediction, and classification of the script by employing the Artificial Neural Network (ANN). For this work, the metaheuristic algorithm inspired by nature called the Firefly Algorithm (FA) is introduced to train the ANN and to solve the problem of optimization. This FA has been based on the movements of the fireflies and their behaviour towards the light. For this, the behaviour of convergence and the performance of this proposed ANN training by using the FA has been analysed with the Back Propagation (BP) algorithm. The results of the simulation have proved the efficiency of computation in the process of training by making use of the technique of FA optimization. Â Â